Transatlantic charismatic renewal, c.1950-2000 - Atherstone, Andrew; Hutchinson, Mark; Maiden, John ca. 20./21. Jh. (Global Pentecostal and charismatic studies, 2021)
"In Transatlantic Charismatic Renewal, c.1950-2000, Andrew Atherstone, Mark Hutchinson and John Maiden bring together leading researchers to examine one of the globally most important religious movements of the twentieth century. Variously referred to as the charismatic 'renewal' or 'revival', it was a key Christian response to globalization, modernity and secularization. Unlike other accounts (which focus either on denominational pentecostalism or charismatic phenomena outside the West), this volume describes transatlantic Christianity drawing deeply on its pneumatic roots to bring about renewal. New research in archives and overlooked journals illuminate key figures from David du Plessis to John Wimber, providing insights which challenge the standard interpretations of the charismatic movement's origins and influence"--